2017
DOI: 10.14569/ijacsa.2017.080727
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Users’ Intentions to Use Mobile Government Applications in Saudi Arabia: TAM Applicability

Abstract: Abstract-M-government applications in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The paper study depends on a modified model that derived from Technology Acceptance Model (TAM) proposed by Davis, (1989). (TAM) model was developed to study the user's acceptance toward new technologies, where it has been conducted to investigate Malaysian citizens toward using the M-Government [42], also it has been conducted by [43] to study the factors that could affect the use of mobile government applications in Saudi Arabia, similarly, it has been used by [8]…”
Section: Paper Model and Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…The paper study depends on a modified model that derived from Technology Acceptance Model (TAM) proposed by Davis, (1989). (TAM) model was developed to study the user's acceptance toward new technologies, where it has been conducted to investigate Malaysian citizens toward using the M-Government [42], also it has been conducted by [43] to study the factors that could affect the use of mobile government applications in Saudi Arabia, similarly, it has been used by [8]…”
Section: Paper Model and Methodologymentioning
confidence: 99%
“…This paper depends on a proposed model that extracted from [8] AS → PU [8] QI → PEOF [8] PU → ATU [42] PEOF → ATU [42] ATU → IU [42] , [43] PEOF → PU [42] Figure 2: The proposed model and hypotheses. The tested model has proved its reliability with Cronbach's Alpha greater than 0.7 that is mean the measurement stays stable over the time and the validity of each factors components was tested in which they return values greater than 0.05 that is acceptable.…”
Section: The Proposed Modelmentioning
confidence: 99%
“…Regarding the conclusions of this study, namely the factors that can influence user acceptance in unequal terms, identify many factors used by previous studies that are mostly different in nature, and often use are showed in this table 1, The figure 2 above shows that the construction of TAM, namely perceived ease of use (PEOU), perceived usefulness (PU), behavior intention (BI), and attitude towards use (AT), are the most common construct to be used to predict user acceptance [8]. The findings show that the Technology Acceptance Model (TAM) is considered the most prominent and empirically proven theory [2] B. Perceived Service Availability (PSA) Service availability is the user's perception that the system used is considered provide connections on the spot.…”
Section: Amentioning
confidence: 99%
“…Results of the current study show that most participants have a positive attitude toward using mgovernment applications. This suggests that citizens will use m-government without any resistance to change and will support the government decision to provide these services [2].…”
Section: Dmentioning
confidence: 99%
“…TOE framework +People [44] TAM+ (TRA) [60] TOE framework [61] TOE model + conceptual model of Cloud Computing adoption [62] TOE framework [63] Technological & Organizational factors [64] TAM [65] First, we discuss the Technology, Organization, and Environment (TOE) Framework, which is a theoretical framework that was developed by Tornatzky and Fleischer in 1990 and still widely used by IS researchers till now [58]. Within this framework, the components of an organization which is studying the adoption of new technology are classified into three major classifications; namely: Technological, Organizational and Environmental elements and the second model to be discussed here is the Technology Acceptance Model (TAM), which is mainly used to examine the user's interaction with the new innovation from two major points.…”
Section: Adoption Model Of Cloud Computing In E-government Authormentioning
confidence: 99%